2022
DOI: 10.1038/s41467-022-33401-x
|View full text |Cite
|
Sign up to set email alerts
|

S100A8-mediated metabolic adaptation controls HIV-1 persistence in macrophages in vivo

Abstract: HIV-1 eradication is hindered by viral persistence in cell reservoirs, established not only in circulatory CD4+T-cells but also in tissue-resident macrophages. The nature of macrophage reservoirs and mechanisms of persistence despite combined anti-retroviral therapy (cART) remain unclear. Using genital mucosa from cART-suppressed HIV-1-infected individuals, we evaluated the implication of macrophage immunometabolic pathways in HIV-1 persistence. We demonstrate that ex vivo, macrophage tissue reservoirs contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…https://doi.org/10.1038/s41564-023-01349-3 tissue macrophages from vsPWH, suggesting that metabolic pathways may control latency in macrophages 41 . In animal models, a myeloid-only mouse model of HIV demonstrated that monocytes and macrophages can sustain infection independently of CD4 T cells 42 and that HIV persists in tissue macrophages during ART suppression 43 .…”
Section: Articlementioning
confidence: 99%
“…https://doi.org/10.1038/s41564-023-01349-3 tissue macrophages from vsPWH, suggesting that metabolic pathways may control latency in macrophages 41 . In animal models, a myeloid-only mouse model of HIV demonstrated that monocytes and macrophages can sustain infection independently of CD4 T cells 42 and that HIV persists in tissue macrophages during ART suppression 43 .…”
Section: Articlementioning
confidence: 99%
“…However, in vitro latent HIV-infected macrophages may shift to glutamate as an energy source and blocking of glutamate resulted in killing of latent infected but not uninfected macrophages [117]. In urethral tissue of PWH, M4 macrophages contained the main HIV reservoir and glycolysis blocking in these cells lead to control of HIV reactivation [31 ▪▪ ]. Together, these data indicate that metabolic interventions specifically targeting latent HIV infected cells may contribute to closing in on reducing the HIV reservoir.…”
Section: Strategies For Reducing Hiv Persistence In Tissuesmentioning
confidence: 91%
“…Macrophages can be long-lived resident immune cells and highly diverse based on their origin and tissue conditions [30]. Considering the participation and compartmentalization of myeloid cells in viral persistence, these cells represent an additional challenge to viral persistence elimination [31 ▪▪ ].…”
Section: Hiv Persistence In Tissue Compartmentsmentioning
confidence: 99%
See 2 more Smart Citations